2021
DOI: 10.3389/fmolb.2021.786070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anemia on Postoperative Cognitive Function in Patients Undergo Hysteromyoma Surgery

Abstract: Cognitive dysfunction is a common disease in aging population. This study aims to compare the influence of different degrees of anemia on the cognitive function of patients undergo hysteromyoma surgery. Sixty-one patients aged 18–60 years who underwent uterine fibroid surgery in the Second Affiliated Hospital of Shantou University Medical College from March 2019 to December 2020 were selected for this study. Patients were divided into three groups: group normal (Group N, patients have no anemia), group of mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Ultimately, it decreases adenosine triphosphate concentrations and causes cell death. [ 43 , 44 ] Cheng Q et al have demonstrated a positive correlation between endothelial progenitor cells (EPCs) and bone mass. [ 45 ] EPCs are capable of secreting bone morphogenetic proteins and other osteoblasts, which promote osteoblast proliferation and differentiation, thus accelerating fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, it decreases adenosine triphosphate concentrations and causes cell death. [ 43 , 44 ] Cheng Q et al have demonstrated a positive correlation between endothelial progenitor cells (EPCs) and bone mass. [ 45 ] EPCs are capable of secreting bone morphogenetic proteins and other osteoblasts, which promote osteoblast proliferation and differentiation, thus accelerating fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…3 It is generally considered that patients' age, history of diabetes and stroke, type of surgery, mode of anesthesia, and intraoperative hypoxia are all risk factors for POCD. 4 The risk of POCD in elderly patients undergoing general anesthesia is higher, and the occurrence of POCD is mainly related to the abnormal cerebral oxygen metabolism in the perioperative period. 5 All tumor operations are performed applying general anesthesia.…”
Section: Introductionmentioning
confidence: 99%